Community Knowledge And Behavior In The Effort To Control Vectors And Dengue Hemorrhagic Fever In Palangka Raya City, Central Kalimantan - Dinindra, Anka Mohamad; Mirza Nuryady, Moh. (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Dengue hemorrhagic fever is a viral disease caused by the dengue virus, which is transmitted through the bite of the Aedes aegypti mosquito. This mosquito species breeds in clean, stagnant water where it lays its eggs. This study aims to assess the public's knowledge and daily practices regarding vector control for dengue fever. An observational study with a cross-sectional design was conducted using a structured questionnaire distributed via Google Forms. The study involved 113 respondents, with 68.1% being under 17 years old. Regarding general awareness, 78.8% (89 individuals) reported being very familiar with dengue fever. In terms of causative knowledge, 88.5% (100 respondents) correctly identified the disease as being caused by the dengue virus transmitted through the bite of Aedes aegypti. For water storage practices at home, 51.3% reported using buckets, 38.1% used bathtubs, and 20.4% used showers without storage. A total of 57.5% identified buckets as potential mosquito breeding sites. Regarding the frequency of cleaning water containers, 46.9% reported doing so weekly. For mosquito control methods, 70.8% stated they used aerosol-based mosquito sprays as part of their routine prevention efforts. Overall, the findings indicate that the community demonstrates a relatively good level of knowledge and proactive behavior in controlling the vector of dengue hemorrhagic fever in their daily lives and environments.